Prelaunch Forecasting of New Automobiles - Urban, Glen L.; Hauser, John R.; Roberts, John H. (Management Science, 1990)
This paper develops and applies a prelaunch model and measurement system to the marketing planning of a new automobile. The analysis addresses active search by consumers, dealer visits, word-of-mouth communication, magazine reviews, and production constraints—issues that are important in understanding consumer response to durable goods. We address these issues with a detailed consumer flow model which monitors and projects key consumer transitions in response to marketing actions. A test-vs.-control consumer clinic provides data which, with judgment and previous experience, are used to “calibrate” the model to fit the sales history of the control car. We illustrate how the model evolved to meet management needs and provided suggestions on advertising, dealer training, and consumer incentives. Comparison of the model's predictions to actual sales data suggests reasonable accuracy when an implemented strategy matches the planned strategy.